Posttraumatic Growth of Victims Informed by the Truth Commission of Ecuador - Reyes Valenzuela, Carlos Marcelo (2018)
This article explores if the victims included in the Truth Commission of Ecuador (TCE, 2010) show Posttraumatic Growth (PTG), the conditions in which it occurs and the kind of events that are associated to it. 48 victims from five provinces in Ecuador were evaluated through the posttraumatic growth inventory. Results show that there are some differences on the level of PTG depending on the number of experiences, the type of violence suffered. Despite this fact, growth does not mean psychological adjustment. This article discusses the implications of such findings and the inconsistencies between PTG and the victims of political violence.